2015
DOI: 10.1097/jom.0000000000000345
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors at Work and Occupational Injury

Abstract: Some psychosocial work factors may play a role in occurrences of occupational injury, but the role is unclear in relation to absence duration for injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
3
10
1
Order By: Relevance
“…Employees filled in a self-administered questionnaire in which their responses were collected about psychosocial work factors and health outcomes. Several articles have already been published by our team using these survey data [ 19 , 25 – 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Employees filled in a self-administered questionnaire in which their responses were collected about psychosocial work factors and health outcomes. Several articles have already been published by our team using these survey data [ 19 , 25 – 29 ].…”
Section: Methodsmentioning
confidence: 99%
“… Thirdly, the associations between occupational exposures and work injury were explored. The results for the associations between psychosocial work factors and work injury were presented in a previous paper and showed that high psychological demands, low social support (especially from supervisors), low reward and its sub-dimensions, low predictability, physical violence, bullying and verbal abuse were associated with work injury [ 19 ]. The associations between the other occupational exposures and work injury were derived from the models above and presented in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A national representative survey in France reported that various adverse workplace practices such as verbal abuse, physical violence, low predictability and bullying, as well as psychological demands and low decision latitude, were related to occupational injuries 23. Furthermore, an important study revealed that organisational injustices such as supervisors' abuse of power can affect both workers' rights as well as their health and safety 24.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of job stress. Recent studies have shown that occupational injury is associated with excessive workload, high cognitive demands and low job satisfaction, high intragroup conflict, job insecurity,19 low decision latitude, conflicts with the supervisor or colleagues,20 lack of organisational support,21 poor physical environment, unfair reward and treatment,22 verbal abuse and low predictability,23 and organisational injustice 24…”
Section: Introductionmentioning
confidence: 99%